2017
DOI: 10.1007/s40997-017-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Static Properties of Magnetorheological Elastomer

Abstract: Your article is protected by copyright and all rights are held exclusively by Shiraz University. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledgement is giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…[9] proposed a new model that utilizes a hyperbolic sine function to represent the hysteresis in order to describe the stiffness and damping characteristics. [10] used MRE as a semi-active vibration isolator to suppress torsional mode of vibration. Results showed that a shift of 3.9 Hz of the natural frequency and slight changes in the damping properties were observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] proposed a new model that utilizes a hyperbolic sine function to represent the hysteresis in order to describe the stiffness and damping characteristics. [10] used MRE as a semi-active vibration isolator to suppress torsional mode of vibration. Results showed that a shift of 3.9 Hz of the natural frequency and slight changes in the damping properties were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Schematic and mathematical representations of different MRE models [7][8][9][10] Schematic representation of models Mathematical expression by the damping force,…”
Section: Introductionmentioning
confidence: 99%
“…These research results show that the mechanical properties and MR effect of MRE can be improved by controlling the concentration and arrangement of magnetic particles. Due to these superior magneto‐mechanical properties, MRE was widely used in vibration isolation, vibration reduction, sensors, and other fields 7‐10 …”
Section: Introductionmentioning
confidence: 99%
“…The MR effect is correlated with the weight fraction of magnetic particles in MREs. Usually the MR effect field-induced modulus was increased with the increase in the weight fraction of magnetic particles (Alias et al, 2018;Lee et al, 2018). The relative MR effect of MREs based on modified magnetic particles was increased because the chain structure of magnetic particles was arrayed more orderly in the rubber matrix (Wen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%